2009
DOI: 10.1007/s00383-008-2318-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of complex minimally invasive surgery in neonates

Abstract: The aim of this study was to assess the feasibility of complex minimally invasive surgery in neonates (and infants <5 kg). A systematic search of databases was performed. Inguinal herniotomy and pyloromyotomy were specifically excluded. Various operations were assessed for operative times, conversion rates, complications and centres performing the procedures. From 479 abstracts, 50 papers were identified describing 1,215 patients. Common operations performed were fundoplication (n = 473), operations for ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
1
8
0
2
Order By: Relevance
“…Moreover, age at surgery has become increasingly younger due to the miniaturization of instruments and evolution of video technology. 4,5 Despite these developments, laparoscopy as a method for treating urological problems has been slower to be adopted in children than in adults. As mentioned previously, the reasons include excellent success rates with open surgery and longer operative times with steeper learning curves for laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, age at surgery has become increasingly younger due to the miniaturization of instruments and evolution of video technology. 4,5 Despite these developments, laparoscopy as a method for treating urological problems has been slower to be adopted in children than in adults. As mentioned previously, the reasons include excellent success rates with open surgery and longer operative times with steeper learning curves for laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, few studies have dealt with laparoscopic renal surgery in infants. Initial reports on urological laparoscopy revealed that children younger than 1 year had more morbidity due to the small working space.…”
mentioning
confidence: 99%
“…Sinha ve ark. 'nın (20) 2010 yılında internet aracılığı ile yaptıkları derlemede (50 adet makale), yenidoğan döneminde yapılan minimal invazif cerrahi girişimler içinde en sık yapılan ameliyatın fundoplikasyon olduğu ve hatta bazı merkezlerin günübirlik laparoskopik Nissen yaptıklarını bildirmiştir (21) .…”
Section: Laparoskopik Fundoplikasyonunclassified
“…Ayrıca torakoskopik girişimde karbondioksit emilimine bağlı olarak nörotoksik yan etkilerin olması, uzun süren hiperkapni ve asidoz olması açık cerrahiyi tercih ettirmektedir (9) . Yenidoğan minimal invazif uygulamalarda (5 kg altı infantlar dahil) en sık açık cerrahiye geçiş oranı %15'tir ve diyafram hernisi onarımında görülmektedir (40) .…”
Section: Konjenital Diafragmatik Herniunclassified
“…The benefits and potential complications of complex minimally invasive surgery (MIS) in pediatrics are well documented [2][3][4][5]. However, there is a lack of published data on the absolute risks of this type of surgery [6].…”
mentioning
confidence: 99%